A high-resolution characterization of the oxide-metal interface in Zircaloy-4 and its relation to the oxidation and hydrogen pickup mechanisms - Sayers, J; Lozano-Perez, S; Nicholls, R; Ortner, S (Elsevier, 2019)
Oxide growth and hydrogen pickup have been measured for Zircaloy-4 in environments of different pH. The metal-oxide interface has been studied at high-resolution over sufficient lengths to show meaningful trends in the behaviour of the ZrO and oxygen-saturated metal layers (suboxides). It was found that suboxide width decreases rapidly at transition, then increases more slowly. The suboxide width is a constant proportion of the dioxide width prior to transition, but drops then increases after transition. Density functional theory was used to predict suboxide stability under different pressures. The behaviour of the suboxide can be explained on the assumption that the dioxide layer is the protective layer until it is bypassed by the environment percolating into the crack network. The relation between hydrogen pickup rate and the oxide behaviour suggests that hydrogen moves across the Zircaloy-4 oxide with no net charge, and that the role of the constrained environment within the cracked fossil oxide requires investigation.